Impact of nutritional status and pulmonary function on short- and long-term overall survival in hemodialysis patients - Özge Aydın Güçlü; Hasim Atakan Erol; Nilüfer Aylin Acet Öztürk; Asli Gorek Dilektasli; Funda Coskun; Abdulmecid Yıldız; Mehmet Karadağ (PLoS ONE, 2025)
Background End-stage renal disease (ESRD) patients frequently experience protein-energy wasting (PEW), which increases their morbidity and mortality rates. Objective This study explores the effects of nutritional status and pulmonary function on the short- and long-term mortality of ESRD patients undergoing hemodialysis. Materials and methods 67 consecutive ESRD patients on maintenance hemodialysis were included in the study. The primary outcomes were all-cause one-year and five-year mortality. Data on demographic characteristics, comorbidities, and laboratory findings were collected. Pulmonary function tests were conducted along with body composition measurements using bioelectrical impedance analysis (BIA). Malnutrition was assessed using the Prognostic Nutritional Index (PNI). Results The median age of the patients was 60.9 ±  12.4 years, with 58.3% being male. Pulmonary function parameters (FEV1 and FVC) were significantly associated with short-term mortality. The PNI was a significant predictor of both short-term and long-term mortality. A PNI score ≤  39.01 was associated with increased short-term mortality (HR: 0.65, 95% CI: 0.48–0.88, p =  0.006), while a score ≤  40 was linked to increased long-term mortality (HR: 0.80, 95% CI: 0.67–0.95, p =  0.015). Additionally, older age (HR: 1.06, 95% CI: 1.01–1.12, p =  0.021) and higher glomerular filtration rate (GFR) (HR: 1.23, 95% CI: 1.02–1.42, p =  0.024) were related to increased long-term mortality risk. Conclusion The study demonstrates that PNI, age, and pulmonary function are critical factors influencing the survival of hemodialysis patients. These findings underscore the importance of comprehensive nutritional and pulmonary assessment to improve clinical outcomes in this population.